POPULATION STRUCTURE OF SANDER MARINUS CUVIER, 1828 IN THE MANGISTAU COAST OF THE MIDDLE CASPIAN (Experimental biology, 2022)
Predatory fish in aquatic ecosystems regulate the abundance of other species, which weakens the tension of competitive relations and stabilizes the community. Walleye refers to large pelagic predators, which, with a high number, effectively eat small and low-value commercial fish, performing a biomeliorative function in the fishing part of the community.At the same time, pike perch is in great demand, both on the foreign and domestic market.  Its meat is considered a dietary product — its fat content is minimal. The nutritional value of walleye is very high — the protein content in it exceeds 18%. Zander meat contains 20 amino acids, 8 of which are irreplaceable (that is, they are not synthesized by the human body), and, in addition, contains a lot of minerals necessary for humans (phosphorus, potassium, iodine, molybdenum, manganese and others).It should also be noted that in Kazakhstan, only ordinary pike perch is caught and exported, the reserves of which are being depleted. Therefore, as an alternative, it is supposed to use a sea walleye.The biological resources of sea pike perch and other marine fish species of the Caspian Sea are not sufficiently exploited, since marine fisheries in our country are poorly developed, and the commercial population of these fish species allows increasing the catch in water areas under the jurisdiction of Kazakhstan. This paper describes the qualitative characteristics of sea zander caught in the research catches of the Mangistau coast of the Middle Caspian, as well as the degree of study in the Caspian Sea and other water bodies. The article describes the methodology for conducting a complete biological analysis of fish and presents statistical data processing. The paper gives a description of the following indicators: size-weight, age, sex ratio. Calculated fatness and determined the rate of size and weight growth in sea zander. Based on the results of these studies, a high correlation was found between age and weight, age and size of fish, and size and weight.
Keywords: Sea pike perch, Middle Caspian coast, length, weight, fatness, age.